Andre Simoens Gallery : Contemporary Art. - Andre Simoens Gallery, Knokke-Heist (Knokke-Zoute : Andre Simoens Gallery)
Alechinsky, Pierre ; Appel, Karel ; Atlan, Jean-Michel ; Basquiat, Jean-Michel ; Bille, Ejler ; Botero, Fernando ; Broodthaers, Marcel ; Christo ; Constant ; Corneille ; Doucet, Jacques ; Dubuffet, Jean ; Gilbert & George ; Jorn, Asger ; Noland, Kenneth ; Van Velde, Bram ; Wunderlich,, Paul ; Zadkine, Ossip
Blauwe catalogus
Engels
boek